Electrochemical Performance Enhancement of VRLA Gel Electrolytes via Polythiophene Addition - Mira, Ziyad; Gencten, Metin (ELECTROCHEMICAL SOC INC, 2026)
In this study, polythiophene, a conductive polymer synthesized through chemical oxidative polymerization, is used for the first time in the literature as an additive to a fumed silica-based gel electrolyte in valve-regulated lead-acid batteries to improve electrochemical performance, charge-transfer characteristics, and ion diffusion pathways. Electrochemical analyses, including cyclic voltammetry, electrochemical impedance spectroscopy, and Tafel extrapolation, are employed to optimize gel systems prepared using three parameters: additive content, stirring duration, and stirring rate. The gel electrolyte containing 0.2 wt% polythiophene, prepared at a stirring time of 30 min and a stirring rate of 500 rpm, exhibits the optimal electrochemical performance. Battery performance is evaluated through galvanostatic charge-discharge experiments, yielding a specific capacity of 51.3 mAh g-1 at a current density of 5 mA g-1, with a capacity retention of 88% over 200 cycles at 10 mA g-1. The incorporation of polythiophene reduces the charge-transfer resistance and enhances ion diffusion, thereby improving the overall electrochemical performance. These results demonstrate that polythiophene is a promising additive for gel electrolytes, offering improved efficiency and cycling stability in valve-regulated lead-acid battery systems. Polythiophene-doped gel exhibits the highest specific capacity of 51.3 mAh g-1 at 5 mA g-1.PTF addition reduces Rs, Rct, and improves ion diffusion pathways.Battery retention reached 88% after 200 cycles at 10 mA g-1.PTF improves the gel network uniformity and enhances redox reversibility.
Keywords: polythiophene additive; polythiophene gel electrolyte; VRLA-gel type batteries; electrochemical optimization; ion diffusion path; LEAD-ACID-BATTERIES; POLYMERIZATION; CONDUCTIVITY; SILICA; Electrochemistry; Materials Science